Systematic Literature Review dalam Strategi Memotivasi Siswa dalam Pembelajaran - Sarnely Uge; Harjun; Ervi Dian Ayu Safitri; Andreanti; La Ode Syarif Hidayatullah; Fita; Sri Rahayu; Sam Safitriani; Alif’ Via Apriliana; Nur Fadillah Annisa; Suci Ramadhani; WD. ST. Febri Wardamianingsih; Tiara Sukmawati (Indo Publishing, 2025)
Learning motivation plays a crucial role in determining students’ success in achieving educational goals, particularly in the 21st century, which emphasizes critical thinking, collaboration, creativity, and communication skills. However, the current learning environment in Indonesia indicates that students’ motivation remains low due to teacher-centered instructional practices and limited interactive engagement. This study aims to explore various teacher strategies for enhancing students’ motivation through a Systematic Literature Review (SLR) approach. The review was conducted in three major stages-planning, implementation, and reporting by analyzing 20 scholarly articles published between 2017 and 2025, obtained from reputable academic databases such as GARUDA, SINTA, and Google Scholar. The findings reveal that several instructional strategies effectively foster learning motivation, including the use of rewards and positive reinforcement, ice breaking activities, Project Based Learning (PjBL), Cooperative Learning, Contextual Teaching and Learning (CTL), and interactive digital media. These strategies consistently promote students’ enthusiasm, confidence, participation, and academic performance. Nevertheless, challenges such as limited resources, teacher preparedness, and diverse student characteristics still hinder optimal implementation. Therefore, strengthening teachers’ pedagogical competence, integrating technology into classroom practices, and applying continuous motivation-oriented evaluation are essential for improvement. The results of this study are expected to provide valuable insights for educators in designing innovative, interactive, and student-centered learning environments that sustainably enhance students’ learning motivation in the modern education era.